Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer: = cos 4x
[tex]\frac{tan2x}{tan4x-tan2x}\\\\=\frac{tan2x}{\frac{2tan2x}{1-tan^{2}2x }-tan2x }\\\\=\frac{tan2x(1-tan^{2}2x) }{2tan2x-tan2x(1-tan^{2}2x) }\\\\=\frac{tan2x(1-tan^{2}2x) }{tan2x(2-1+tan^{2}2x) }\\\\=\frac{1-tan^{2}2x }{1+tan^{2}2x } \\\\=\frac{1-\frac{sin^{2}2x }{cos^{2}2x } }{1+\frac{sin^{2}2x }{cos^{2}2x } }\\\\=\frac{cos^{2}2x-sin^{2}2x }{cos^{2}2x+sin^{2}2x } \\\\=\frac{cos4x}{1}\\\\=cos4x[/tex]
Step-by-step explanation:
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.